Iklan Online di Media Sosial : Risiko dan Kepercayaan Pengguna terhadap Iklan Online di Line@ dengan Metode Structural Equation Modelling (SEM) Studi Kasus : Line@ Berrybenka - Maharani Essraningtiyas; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Online advertising is a media used by organizations or individuals to introduce products or services to the public on the internet. This study discusses the positive and negative impacts of online advertising. The model used is TAM (Technology Acceptance Model) combined with trust and perceived risk and analyzed by Structural Equation Modeling (SEM) in Line@ as a case study with 229 sample data. The results shows that user intention to transact online is not determined by the usefulness of online advertising as well as the ease of use of the system but because they accept and develop a positive attitude towards online advertising. In addition, the intention of users to transact online is also influenced by perceived risk because a part from considering the positive impact, users also consider the negative impact of online advertising before doing transactions on line@